(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is conducted to analyse the reasons for cyberbullying and the effects of cyberbullying on social media among female students at a university in Northern Peninsular Malaysia. One hundred female students participated in this study through online survey. Majority of the respondents are well-versed pertaining to cyberbullying and are not involved in cyber bullying. The results indicate that female students are exposed to cyberbullying on social media, namely Instagram, Facebook and Twitter and others. This is because the female students use social media daily and are more insecure and sensitive on the words hurled in social media.